2005
DOI: 10.1163/156854105774384796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nematode infection and mulching on the yield of plantain (Musa spp., AAB-group) ratoon crops and plantation longevity in southeastern Nigeria

Abstract: The effects of nematode infection and mulching on plantain cv. Agbagba (Musa spp., AAB-group, false horn) yield and plantation longevity were examined in a field experiment at the High Rainfall Station of the International Institute of Tropical Agriculture (IITA) at Onne in southeastern Nigeria. The 2nd, 3rd and 4th crop cycles (1st, 2nd and 3rd ratoon, respectively) following the plant crop cycle (mother crop) were examined in nematode inoculated or non-inoculated and mulched or nonmulched treatments. Nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, little is known about the effect of the environment on nematodes and how these parasites can affect banana growth and production. Available data in the literature mostly reported on the effects of mulching and intercropping on the propagation of Radopholus similis and Helicotylenchus multicinctus (Auwerkerken et al, 2005), R. similis interactions (Bwamiki, 2004), and root damage due to colonization by P. goodeyi in plants grown under suboptimal conditions (Talwana et al, 2003). In general, the microenvironment has a strong effect on nematodes, which help indicate soil health status and many soil functions (Gebremikael et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the effect of the environment on nematodes and how these parasites can affect banana growth and production. Available data in the literature mostly reported on the effects of mulching and intercropping on the propagation of Radopholus similis and Helicotylenchus multicinctus (Auwerkerken et al, 2005), R. similis interactions (Bwamiki, 2004), and root damage due to colonization by P. goodeyi in plants grown under suboptimal conditions (Talwana et al, 2003). In general, the microenvironment has a strong effect on nematodes, which help indicate soil health status and many soil functions (Gebremikael et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This may not be unrelated to the higher growth rate of the mulched plants. The early flowering would result in a situation where the plantain fruits matured faster and are harvested earlier thus increasing the cycling rate of the mats (Rotimi et al, 2004b;Coyne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to multiple reasons, including the modification of the rhizosphere soil microbial community, which becomes richer and more populated with mulching. Studies on plantain in West Africa have consistently demonstrated the improved productivity and longevity of plantations infected with nematodes following mulching, irrespective of the type of mulch [137,[142][143][144], and similarly elsewhere on other banana types [140,145,146]. The regular application of relatively small amounts of fresh Tithonia diversifolia leaf material to plantain heavily affected by nematodes in Nigeria demonstrated great beneficial effects on crop performance [147].…”
Section: Effects Of Banana Cropping Systems On Nematodesmentioning
confidence: 99%